Hand Hygiene Effectiveness in Controlling the Spread of COVID-19: A Scoping Review - Dyah Suryani; Tating Nuraeni; Erni Buston; Lia Fentia; Supriatin Supriatin; Lili Amaliah; Silvia Anitasari (Jurnal Penelitian Pendidikan IPA, 2023)
Encouraging proper hands, including regular handwashing with soap and water or the use of hand sanitizers, is crucial in preventing the transmission of COVID-19 and other infectious diseases. This preventive measure helps to eliminate or reduce the presence of the virus on hands, particularly after contact with potentially contaminated surfaces or objects. The study was comprehensively searching databases and other sources to identify literature on hand hygiene and COVID-19 between 16 April, 2020 and 30 May 2023. We analyzed various aspects of the retrieved articles and studies, including the sources, publication dates, types and topics covered. In the initial stage of the review process, the researchers identified 463 records from various sources. After removing 56 duplicate records, they were left with 407 unique articles for further screening. During the screening process, 280 articles were excluded for various reasons. This resulted in 127 articles that passed the initial screening. The next step involved assessing the eligibility of the full text of these 127 articles. Out of these, 108 articles were excluded based on the eligibility criteria, and the research obtained the full texts of the remaining 19 articles for further analysis. By creating a collective awareness and understanding of the importance of hand hygiene, we can create a positive impact on public health and reduce the transmission of diseases such as COVID-19